-3(6p+5)-2(5-17p)=3(9+5p)

Simple and best practice solution for -3(6p+5)-2(5-17p)=3(9+5p) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(6p+5)-2(5-17p)=3(9+5p) equation:


Simplifying
-3(6p + 5) + -2(5 + -17p) = 3(9 + 5p)

Reorder the terms:
-3(5 + 6p) + -2(5 + -17p) = 3(9 + 5p)
(5 * -3 + 6p * -3) + -2(5 + -17p) = 3(9 + 5p)
(-15 + -18p) + -2(5 + -17p) = 3(9 + 5p)
-15 + -18p + (5 * -2 + -17p * -2) = 3(9 + 5p)
-15 + -18p + (-10 + 34p) = 3(9 + 5p)

Reorder the terms:
-15 + -10 + -18p + 34p = 3(9 + 5p)

Combine like terms: -15 + -10 = -25
-25 + -18p + 34p = 3(9 + 5p)

Combine like terms: -18p + 34p = 16p
-25 + 16p = 3(9 + 5p)
-25 + 16p = (9 * 3 + 5p * 3)
-25 + 16p = (27 + 15p)

Solving
-25 + 16p = 27 + 15p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-15p' to each side of the equation.
-25 + 16p + -15p = 27 + 15p + -15p

Combine like terms: 16p + -15p = 1p
-25 + 1p = 27 + 15p + -15p

Combine like terms: 15p + -15p = 0
-25 + 1p = 27 + 0
-25 + 1p = 27

Add '25' to each side of the equation.
-25 + 25 + 1p = 27 + 25

Combine like terms: -25 + 25 = 0
0 + 1p = 27 + 25
1p = 27 + 25

Combine like terms: 27 + 25 = 52
1p = 52

Divide each side by '1'.
p = 52

Simplifying
p = 52

See similar equations:

| x^2-17=81 | | 5/6-x/18=1/9 | | 7b=3-2b | | 4.71=3.14a(2) | | (-5x)+3x= | | 43+34= | | 2w=40 | | 2x^2+8x+8=8 | | 3x-15=8x+7 | | 16=.25h | | -9-8(1.4H)=-17 | | -2y=3y+5 | | -12=3x+9-6x | | 25-3x=1 | | 2(l+0.4l)=364 | | 56-(3c+4)=4(c+7)+3 | | 0.07y+0.02x=5 | | 9x-12+85=0 | | -3/4r-1 | | U^2-3v=0 | | -z/2 | | (2x+8)+(3x+16)+(4x-18)+(3x-7)+(2x+25)=720 | | 8+4v=-4 | | 4a+6-3a-2= | | S/-3=2 | | h=2*3.14*r^2+2*3.14*r*16.2 | | 25n-40=-62 | | 3/4(8y-12)= | | .75t=50 | | F(x)=12x-6 | | 8(-5+4)= | | .75t=.50 |

Equations solver categories